SantaMan: a Christmas crusade [videorecording (DVD)] - Stern, Bret (Gravitas Ventures, 2022)
Fed up with the growing number of 'Naughty-Listers,' Santa becomes a superhero dubbed SantaMan. Donning a new red suit and a buffet of gadgets that rivals Batman, Santa sets out to turn those bad apples into do-gooders.